Investigating the Immune System in Parkinson's Disease - Mac Mahon Copas, Adina Nicole (Trinity College Dublin. School of Medicine. Discipline of Physiology, 2024)
In 1817 James Parkinson first described the symptoms of the Parkinson's disease (PD). It is the second most common neurodegenerative disease worldwide, and cases are rising exponentially. Characteristic hallmarks of PD include loss of dopaminergic neurons of midbrain, as well as alpha synuclein containing inclusions known as Lewy bodies. In recent years, the involvement of immune-related processes such as microgliosis and astrogliosis n disease pathogenesis has been recognised. Furthermore, the infiltration immune cells from the periphery into the brain parenchyma in PD has been described. While these cells have been demonstrated to induce neuronal damage, their effects on astrocytes remains to be elucidated. Therefore this thesis aimed to investigate the role of inflammation in contributing to PD, with particular focus on T lymphocytes and astrocyte reactivity. To do this induced pluripotent stem cells (iPSC) were used to generate, midbrain astrocytes. Following this, the effects of CD4+ T cell associated cytokines on the astrocytes was investigated. This study demonstrated these cytokines were capable of inducing gene expression, protein secretion and morphological changes consistent with reactive astrocytes in the iPSC derived astrocytes. The response generated was chronic and pro-inflammatory in nature. Furthermore, increased DNA damage marker, yH2AX and an increased levels of lactate dehydrogenase, indicating membrane damage were observed in the midbrain astrocytes. In order to increase translatability, this thesis aimed to derived iPSC from PD individuals. Skin biopsies were collected to generate fibroblasts which were reprogrammed back to a pluripotent state. The cells generated expressed markers of pluripotency and exhibited the pluripotent ability to differentiate cells of the three germ layers. From these PD iPSC, midbrain astrocytes were derived. Following this, the astrocytes were stimulated with cytokines to stimulate a reactive phenotype. Interestingly, the PD derived astrocytes demonstrated a more prominent inflammatory phenotype compared to the control astrocytes. Finally, collected blood samples were analysed to assess differences in peripheral immune cell populations between PD and healthy age-matched control individuals. While no differences were observed in plasma ⍺-syn or inflammatory cytokines, a number of differences were observed in the cytokines produced by peripheral mononuclear cells and more specifically, CD4 and CD8 T cells. Overall , the data generated in this thesis adds to current literature suggesting a prominent role for peripheral and central immune cell activation in contributing to PD pathogenesis. Future work to expand on the data presented here could aid in identification of immune-based targets for the treatment of PD.
APPROVED
Keywords: Parkinson's disease; Neuroinflammation; Astrocytes; Induced pluripotent stem cells; T cells; Peripheral immune system; Cytokines